Applicability Principle Legality inside Special Criminal Acts: Case Studies on Narcotics Crime - Muklisin Muklisin (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2022)
This article analyses the juridical application of criminal law in cyberbullying cases in Indonesia. The rise of digital platforms has exacerbated cyberbullying incidents, highlighting gaps in existing criminal legislation. The research aims to explore these gaps and the challenges in enforcing legal provisions against perpetrators. Employing a normative juridical method, the study examines the legal framework surrounding cyberbullying, including relevant case studies to illustrate judicial practices. The findings reveal that while existing laws address cybercrime, they often fail to provide sufficient protection for victims of cyberbullying. The lack of specific legal provisions tailored to online harassment creates legal ambiguity, resulting in inconsistent verdicts. This study suggests enhancing the current legal framework by incorporating clear definitions and legal parameters for cyberbullying, thus improving victim protection and ensuring more consistent legal outcomes. The study contributes to the ongoing discussion on the intersection of law and technology, proposing legal reforms to better address modern cyber threats.